HEALTH RELATED QUALITY OF LIFE (HRQoL) IN CHRONIC KIDNEY FAILURE PATIENTS AT ARIFIN AHMAD REGIONAL GENERAL HOSPITAL RIAU PROVINCE - Octavia, Rickha; Sari, Seftika; Nisa', Fitriatun (Faculty of Mathematic and Natural Science, Garut University, 2024)
After tuberculosis, the illness with the highest death rate is chronic kidney failure. Renal function declines in patients with chronic kidney failure until, eventually, they are unable to filter and eliminate the body's electrolytes at all. Metrics about quality of life are necessary because the patient's health will suffer if medical therapy fails. This research aims to determine the description of health-related quality of life (HRQoL) in chronic kidney failure patients at the Arifin Achmad Regional General Hospital, Riau Province. The samples used in this study were chronic kidney failure patients who underwent treatment at the Arifin Achmad Regional General Hospital, Riau Province, in the period January-December 2022 and met the inclusion and exclusion criteria. This study is observational and descriptive. Non-probability sampling was employed to select 74 participants for the study. Based on the results of research that has been carried out regarding the description of health-related quality of life (HRQoL) in patients with chronic kidney failure at the Arifin Achmad Regional General Hospital, Riau Province, it was found that chronic kidney failure has an impact on the quality of life in health with an average utility value of EQ-5D -5L and VAS namely 0.6235 and 0.7177. Anxiety or depression (40.5%) and pain or discomfort (52.7%) were the most commonly reported health issues.